Analisis Pengaruh Marketing Mix terhadap Keputusan Taruna/I Memilih Kampus Politeknik Pelayaran Banten - Dapid Rikardo; Adnan Adnan; Joni Turiska (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This research has a purpose. the influence of the marketing mix on the cadets' decision to choose the Banten Shipping Polytechnic campus. The research was carried out at Poltekpel Banten, carried out from January 2020 to May 2020. The research method used in this study was quantitative. The data collection method for primary data was obtained from individual responses to questionnaires distributed directly. The research process was deductive. This study's population was Poltekpel Banten alumni, with a total sample of 199 cadets. The instrument used in measuring the simulation learning media is a questionnaire. The results showed that of the seven hypotheses tested in this study, seven positive and significant hypotheses were found to the Taruna/I decided to choose the Banten Shipping Polytechnic campus. In conclusion, there is a positive and significant influence for all Marketing Mix variables studied on the Taruna/I Decision to Choose the Banten Shipping Polytechnic Campus Keywords: Institutional Management, Marketing Mix, Youth Decisions,